2008
DOI: 10.1143/jjap.47.8935
|View full text |Cite
|
Sign up to set email alerts
|

Study on Surface Modification of Indium Tin Oxide and Resist Surfaces Using CF4/O2 Plasma for Manufacturing Organic Light-Emitting Diodes by Inkjet Printing

Abstract: The paper describes experiments on a metal ball rolled along parallel metal rails. An electrical force is developed on the ball in the direction of movement by passing current through it from one rail to the other. Contrary to the electromagnetic theory of the ball-bearing motor, the electrical force on a brass ball is of the same order as that on a steel ball. The results are discussed in terms of a torque exerted in the contact region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…4(a) and (b), respectively. The untreated ITO (sample A) consists of three different carbon environments at 284.6 eV for C C, at 286.2 eV for C O (ethers and/or epoxy), and at 288.6 eV for O C O (esters) [39]. From the C 1s spectrum of the GOPTS-SAM-treated ITO (sample C), increase in C O bonds was observed, which are attributed to epoxy functionality in chemical structure of GOPTS-SAM (see also Supplementary Fig.…”
Section: Surface Analyses Of Ito Anode and Cathodementioning
confidence: 99%
“…4(a) and (b), respectively. The untreated ITO (sample A) consists of three different carbon environments at 284.6 eV for C C, at 286.2 eV for C O (ethers and/or epoxy), and at 288.6 eV for O C O (esters) [39]. From the C 1s spectrum of the GOPTS-SAM-treated ITO (sample C), increase in C O bonds was observed, which are attributed to epoxy functionality in chemical structure of GOPTS-SAM (see also Supplementary Fig.…”
Section: Surface Analyses Of Ito Anode and Cathodementioning
confidence: 99%
“…4 5 Printing technologies are thus envisaged to pave the way for frontier flexible electronics, such as flexible displays, sensors, and radio frequency identification cards. [6][7][8] Among various printing methods, the basic concepts of nano-imprint lithography and transfer printing are widely adapted to the transfer of all the components, i.e., metal electrodes, insulators, and semiconductors, needed to fabricate thin-film transistors (TFTs) on a plastic substrate. For examples, Menard et al reported bendable TFTs fabricated by transferring free standing micro-structured * Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…As mold precursors, acrylic mixtures were prepared from silsesquioxane-based materials, silicone acrylate, poly(propylene glycol) diacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl methacrylate, and photoinitiator. By using these materials, the replica molds were fabricated from a silicon master onto a flexible substrate by means of UV-assisted molding process at room temperature.…”
mentioning
confidence: 99%
“…The pattern accuracy may be increased by steering the ink spreading using local patterns on the substrate surface. One approach involves prepatterning banks of insulator materials onto the substrate to concentrate the ink into defined areas 6, 7. Prepatterning processes, however, have unfortunately presented an obstacle to the production of large‐area displays: prepatterning processes rely on conventional photolithographic techniques that are complicated and relatively costly.…”
Section: Introductionmentioning
confidence: 99%